CROSS CULTURAL UNDERSTANDING: THE BRIDGE TO MINIMIZE AMERICAN CULTURE SHOCK - Iftanti, Erna (Research Collections, 2013)
In the name of Allah the Most Beneficent and the MostMercifulPraise be to Allah SWT for His blessing and love which enable the writer to have power and time to finish this book.The writer would like to address her greatest gratitude and thanks to her beloved husband and children for their support and understanding in developing this book entitled Cross Cul- tural Understanding: the Bridge to Minimize American Culture Shock.This book has three main chapters. The first chapter is theConcept of Cross Cultural Understanding, the second chapter is The Bridge to Minimize Cross Cultural Understanding, and the last chapter is American Culture Shock.Many people who go abroad encounter features in their host culture that they may find disturbing. Reaction to these alien aspects of the new culture can dampen the entire experience in the country, resulting in various kinds of negative reactions. To adapt positively and effectively to the host culture, it is neces- sary to overcome the negative responses.Therefore, this book is hopefully able to help people to overcome the negative responses to cross cultural understand- ing and especially to minimize the possibility of experiencing American culture shock.Finally, criticisms and suggestions is very valuable to im- prove this paper